2020
DOI: 10.4049/jimmunol.1900799
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity with Self-Antigen Tunes the Functional Potential of Naive B Cells Specific for Foreign Antigens

Abstract: Upon Ag exposure, naive B cells expressing BCR able to bind Ag can undergo robust proliferation and differentiation that can result in the production of Ab-secreting and memory B cells. The factors determining whether an individual naive B cell will proliferate following Ag encounter remains unclear. In this study, we found that polyclonal naive murine B cell populations specific for a variety of foreign Ags express high levels of the orphan nuclear receptor Nur77, which is known to be upregulated downstream o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Purified antigens were biotinylated using an EZ-Link Sulfo-NHS-LCBiotinylation kit (Thermo Fisher Scientific) using a 1:1.3 M ratio of biotin to Ag. To make tetramers, biotinylated Ags were mixed with streptavidin–PE (PJ27S; ProZyme) at the ratio determined or at a 5 to 1 ratio using the biotin concentration provided by the manufacturer as described before 86 . Following a 30-min incubation on ice, unconjugated biotinylated Ag was often removed by several rounds of dilution and concentration using a 100 kDa Amicon Ultra (MilliporeSigma) or 300 kDa Nanosep centrifugal devices (Pall).…”
Section: Methodsmentioning
confidence: 99%
“…Purified antigens were biotinylated using an EZ-Link Sulfo-NHS-LCBiotinylation kit (Thermo Fisher Scientific) using a 1:1.3 M ratio of biotin to Ag. To make tetramers, biotinylated Ags were mixed with streptavidin–PE (PJ27S; ProZyme) at the ratio determined or at a 5 to 1 ratio using the biotin concentration provided by the manufacturer as described before 86 . Following a 30-min incubation on ice, unconjugated biotinylated Ag was often removed by several rounds of dilution and concentration using a 100 kDa Amicon Ultra (MilliporeSigma) or 300 kDa Nanosep centrifugal devices (Pall).…”
Section: Methodsmentioning
confidence: 99%
“…In anticipation of administering these antibodies in vivo , we confirmed that none bound to permeabilized HEp-2 cells ( Fig. 3f ), a common assessment of autoreactivity 28,29 .…”
Section: Resultsmentioning
confidence: 57%
“…In anticipation of administering these antibodies in vivo , we confirmed that none bound to permeabilized HEp-2 cells ( Figure 3d ), a common assessment of autoreactivity. 28 , 29 …”
Section: Resultsmentioning
confidence: 99%
“…In anticipation of administering these antibodies in vivo, we confirmed that none bound to permeabilized HEp-2 cells (Figure 3d), a common assessment of autoreactivity. 28,29 We next performed cross-competition binding experiments to gauge the antigenic sites on HPIV3 preF allowing for neutralization. Three of these five new neutralizing mAbs (PI3-E12, -A3, and -B5) fully competed with each other and the previously described antibody PIA174 (Figure 4a).…”
Section: Binding and Neutralization Of Hpiv3 Within The Human B Cell Repertoirementioning
confidence: 99%